Public reason and religion: the theo-ethical equilibrium argument for restraint - Billingham, P (Springer Netherlands, 2017)
Most public reason theorists believe that citizens are under a ‘duty of restraint’. Citizens must refrain from supporting laws for which they have only non-public reasons. The theo-ethical equilibrium argument purports to show that theists should accept this duty, on the basis of their religious convictions. Theists’ beliefs about God’s nature should lead them to doubt moral claims for which they cannot find secular grounds, and to refrain from imposing such claims upon others. If successful, this argument would defuse prominent objections to public reason liberalism. This paper assesses the theo-ethical equilibrium argument, with a specific focus on Christian citizens. I argue that Christians should seek theo-ethical equilibrium, but need not endorse the duty of restraint. I establish this in part through examining the important theological concept of natural law. That discussion also points to more general and persistent problems with defining ‘public reasons’.